Correlation of Brain Ultrasonography Scans to the Neuromotor Outcome of Very-Low-Birth-Weight Infants During the First Year of Life. (November 2014) - Karagianni, Paraskevi; Rallis, Dimitrios; Kyriakidou, Maria; Tsakalidis, Christos; Pratsiou, Paraskevi; Nikolaidis, Nikolaos
To evaluate the consistency of the Hammersmith Infant Neurological Examination scores of very-low-birth-weight infants at 6 and 12 months of age and its correlation to cranial ultrasonography findings, we designed a prospective study between January 2005 and January 2008, in the tertiary Neonatal Unit of Aristotle University of Thessaloniki, Greece. All infants enrolled had a cranial ultrasonography performed at term. Preterm infants born at <32 weeks gestation with a birth weight <1500 g were eligible for the study. One hundred seventy-four infants were finally enrolled; out of those, 46 (26%) had an optimal score at 6 and 76 (44%) at 12 months of age. Mean global scores were 61 and 69 at 6 and 12 months, respectively. The Hammersmith Infant Neurological Examination score significantly increased between 6 and 12 months, equally in all ultrasonography groups. The presence of cystic periventricular leukomalacia was associated to lower scores and neurologic impairment.